CORPORATE GOVERNANCE DAN FAKTOR LAINNYA YANG MEMENGARUHI PENGHINDARAN PAJAK - MUNGNIYATI; ELVA EVELYN FRANATA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
Tax avoidance is a strategy used by companies to reduce tax obligations by exploiting loopholes in tax regulations legally. This study aims to obtain empirical evidence on the effect of independent board of commissioners, board size of directors, board gender diversity, institutional ownership, managerial ownership, and leverage as independent variables on tax avoidance as the dependent variable. The research objects are manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The sample was selected using a purposive sampling method, resulting in 145 companies with a total of 435 observations. Data were analyzed using multiple linear regression with software IBM Statistical Package for the Social Sciences (SPSS) version 25. The results of this search indicate that independent board of commissioners, board size of directors, board gender diversity, institutional ownership, managerial ownership, and leverage have no effect on tax avoidance.